Edukasi Kesehatan Preventif sebagai Strategi Pencegahan Kenakalan Remaja di Lingkungan Pendidikan Menengah - Rini Susanti; Irma Fitrilia; Juanna Soehardy; Alif Rahman Habibi; Rika Irawan; Suryani Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Juvenile delinquency in secondary education environments is a multidimensional problem that includes violent behavior, bullying, and risky sexual behavior, which impacts adolescents' psychosocial development and the school climate. This study aims to analyze the role of preventive health education as a strategy to prevent juvenile delinquency in secondary education settings. The study uses a descriptive qualitative design with a contextual approach, conducted at a secondary school in an urban area. The research subjects include students, teachers, and guidance counselors directly involved in preventive health education activities. Data collection techniques were carried out through observation, semi-structured interviews, and document studies, while data analysis employed thematic analysis with source and technique triangulation. The research results indicate that preventive health education conducted through counseling and interactive discussions can increase adolescents' understanding of the concepts of violence, bullying, and the risks of risky sexual behavior. Students showed increased awareness of healthy behavioral boundaries, openness in discussions, and active participation during activities. Teachers and counselors assessed that preventive health education helps in efforts to prevent adolescent problems in schools. This study concludes that preventive health education plays a strategic role in preventing juvenile delinquency and needs to be sustainably integrated into school programs to support healthy and adaptive adolescent development.